An aqueous synthesis of porous PtPd nanoparticles with reversed bimetallic structures for highly efficient hydrogen generation from ammonia borane hydrolysis. Issue 2 (12th December 2019) - Yao, Kaisheng; Zhao, Chenchen; Wang, Nan; Li, Tianji; Lu, Weiwei; Wang, Jianji
Abstract : Porous PtPd NPs with reversed bimetallic structures from Pd-on-Pt to Pt-on-Pd can be one-pot prepared in aqueous solution under the modulation of [C16 mim]Cl and glycine and show superior catalytic activities for AB hydrolysis to produce hydrogen. Abstract : Fine construction of porous bimetallic nanomaterials with tunable components and structures is of great importance for their catalytic performance and durability. Herein, we present a facile and mild one-pot route for the preparation of porous PtPd bimetallic nanoparticles (NPs) with reversed structures in aqueous solution for the first time. To this end, a common ionic liquid (IL) 1-hexadecyl-3-methylimidazolium chloride ([C16 mim]Cl) is utilized to direct the growth and assembly of porous structures of PtPd NPs. It is shown that the as-prepared porous Pt25 Pd75 NPs have obvious hierarchical structures with nanoflowers as subunits and nanorods as basic units. The elemental components and structures of the porous PtPd NPs can be tuned by the precursor ratio and the [C16 mim]Cl concentration. Furthermore, various porous PtPd bimetallic structures from Pd-on-Pt to Pt-on-Pd may be efficiently switched by controlling the concentration of glycine. Owing to their high specific surface area, porous hierarchical structures (including mesopores and micropores), and probable electronic effects between Pt and Pd, the porous Pt25 Pd75 NPs (Pd-on-Pt structure) are found to exhibit prominent catalytic activity and high stability for hydrogen production from hydrolysis of ammonia borane.